Seroprevalence of T. cruzi infection in Canis familiaris, state of Sucre, Venezuela - Berrizbeitia, Mariolga; Concepcion, Juan Luis; Carzola, Valentina; Rodríguez, Jessicca; Cáceres, Ana; Quiñones, Wilfredo (Biomédica, 2013)
Introduction: Trypanosoma cruzi infection in humans has been extensively studied in Venezuela; however, in reservoirs it has been less investigated. Objective: The objective of this study was to determine the seroepidemiology of T. cruzi in the state of Sucre, Venezuela. Materials and methods: A cross-sectional and prospective study conducted in 95 towns and 577 dwellings in the 15 municipalies of the state of Sucre, Venezuela, from August to November, 2008. The evaluation of serum samples was performed with the CruziELISA kit and the multiple antigens binding assays (MABA). Furthermore, epidemiological surveys were applied to evaluate the risk factors. Results: A total of dogs (average age of 2, 6 + 2.2 years, 226 males and 137 females) was evaluated. The combination of the ELISA / MABA tests detected 78 positive sera, sixty-nine negative and 10 of inconclusive results. The seroprevalence of the T. cruzi infection in dogs in the state of Sucre, was 22.1% (CI 95%: 20.58-22.4%). No significant statistic association was found between the T. cruzi infection in dogs and the evaluated epidemiological variables: hunting dogs that slept oudoors roaming freely in the populated center, sex of the animal and eating habits. The T. cruzi infection was associated to the age of canines, being significantly higher in the group of 0 to 3 years, when compared with older dogs. Conclusions: The high T. cruzi seroprevalence dected in dogs shows that in this región of Venezuela there prevails an important risk factor of transmissibility of this parasite to human populations. doi: http://dx.doi.org/10.7705/biomedica.v33i2.760